2015
DOI: 10.1002/2015wr017081
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lateral confinement on gravel bed river morphology

Abstract: In this paper, we use a physical modeling approach to explore the effect of lateral confinement on gravel bed river planform style, bed morphology, and sediment transport processes. A set of 27 runs was performed in a large flume (25 m long, 2.9 m wide), with constant longitudinal slope (0.01) and uniform grain size (1 mm), changing the water discharge (1.5-2.5 L/s) and the channel width (0.15-1.5 m) to model a wide range of channel configurations, from narrow, straight, embanked channels to wide braided netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
66
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 39 publications
7
66
0
Order By: Relevance
“…Experiment 1 seems to have a greater bedload transport rate than would be expected for the range of active widths, which is either an artifact of the low detection rates for that experiment (i.e. The dimensionless morphological active width While previous measurements of the morphological active width are relatively limited, Bertoldi et al (2009a), Ashmore et al (2011), andLugo et al (2015) showed that the variation of active width with discharge or total stream power may collapse to a general function using dimensionless stream power (ω*) and active width ratio (non-dimensionalized using wetted width). The correlation of the morphological active width with directly measured bedload transport rate in braided rivers at constant discharge and under varying flow conditions has not previously been demonstrated.…”
Section: Volumes Of Changementioning
confidence: 87%
See 4 more Smart Citations
“…Experiment 1 seems to have a greater bedload transport rate than would be expected for the range of active widths, which is either an artifact of the low detection rates for that experiment (i.e. The dimensionless morphological active width While previous measurements of the morphological active width are relatively limited, Bertoldi et al (2009a), Ashmore et al (2011), andLugo et al (2015) showed that the variation of active width with discharge or total stream power may collapse to a general function using dimensionless stream power (ω*) and active width ratio (non-dimensionalized using wetted width). The correlation of the morphological active width with directly measured bedload transport rate in braided rivers at constant discharge and under varying flow conditions has not previously been demonstrated.…”
Section: Volumes Of Changementioning
confidence: 87%
“…To date, field data on braided river channel topography is limited by low spatial and temporal frequency and a lack of simultaneous bedload transport rates (Bertoldi et al, 2010;Church and Ferguson, 2015;Williams et al, 2016b;Vericat et al, 2017). These data and corresponding analysis can inform, assess, and assist in developing numerical models of braiding morphodynamics and bedload flux (Bertoldi et al, 2009a;Williams, 2012;Church and Ferguson, 2015;Lugo et al, 2015), which require calibration and validation with high-resolution 3-dimensional surveys of braided rivers (Williams et al, 2016a;Redolfi et al, 2017). These data and corresponding analysis can inform, assess, and assist in developing numerical models of braiding morphodynamics and bedload flux (Bertoldi et al, 2009a;Williams, 2012;Church and Ferguson, 2015;Lugo et al, 2015), which require calibration and validation with high-resolution 3-dimensional surveys of braided rivers (Williams et al, 2016a;Redolfi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations